Pachymic acid alleviates metabolic dysfunction-associated steatotic liver disease by inhibiting ferroptosis through PPARα - Ren, Guilin; Lin, Yiyou; Qiu, Jiannan; Zhang, Congcong; Chen, Lin; Zhu, Linwensi; Fan, Xiaohui; Dou, Xiaobing; Liu, Qingsheng (Frontiers in Pharmacology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is characterized by excessive lipid deposition in hepatocytes without a history of significant alcohol consumption. Pachymic acid (Pac), a bioactive triterpenoid from Poria cocos, has shown promise in treating MASLD due to its antioxidant and anti-inflammatory capabilities. This study aimed to elucidate the molecular impact and mechanisms of Pac in MASLD.MethodsMale C57BL/6J mice were subjected to a high-fat diet (HFD) for 8 weeks, followed by a 4 weeks treatment with the Pac. Comprehensive assessments including physiological, biochemical, and histomorphological evaluations were performed post-treatment. Transcriptomic analysis of liver samples from normal control (NC), HFD, and HFD + high-dose Pac (Pac-H) groups was conducted, with validation through Western blot, and immunofluorescence.ResultsHFD induced biochemical abnormalities and liver injury, which were significantly reversed by Pac, as evidenced by decreased plasma levels of AST (Aspartate aminotransferase), ALT (Alanine aminotransferase), TG (Triglyceride), and TC (Total cholesterol), and reduced hepatic TG and TC levels. Pac also mitigated lipid accumulation, peroxidation, and ferroptosis. Pac modulated the expression of PPARα (Peroxisome proliferator-activated receptor α), MAPKs (Mitogen-activated protein kinases), and ferroptosis pathways, thereby ameliorating MASLD.DiscussionThe study demonstrated that Pac inhibited the MAPKs signaling pathway and reduced hepatic ferroptosis, alleviated steatosis through PPARα regulation, offering a potential therapeutic strategy for MASLD.